UJI AKTIVITAS ANTIMIKROBA BAKTERI ASAM LAKTAT CAIRAN RUMEN TERHADAP PERTUMBUHAN Salmonella Enteritidis, Bacillus cereus, Escherichia coli DAN Staphylococcus aureus MENGGUNAKAN METODE DIFUSI SUMUR AGAR - Frans Umbu Datta; Angela Novita Daki; Imanuel Benu; Annytha Ina Rohi Detha; Nancy D. F. K. Foeh; Nemay A. Ndaong (JURNAL KAJIAN VETERINER, 2019)
Rumen liquid is a waste product of slaughterhouse that has the potential to be a pollutant, contains lactic acid bacteria which can be used as bio preservatives in food. The purpose of this study was to identify the antimicrobial activity of lactic acid bacteria (LAB) isolates from rumen fluid against Gram positive and Gram negative bacteria using well diffusion and disc diffusion methods and using lactic acid bacteria isolates (supernatant) and non-filtrate from rumen fluid. The main research materials used were LAB rumen fluid isolates, MRSA media (Mann Rogosa Sharpe Agar), MRSB media (Mann Rogosa Sharpe Broth), MHA media (Muller Hinton Agar), and pathogenic bacteria Bacillus cereus, Staphylococcus aureus, Escherichia coli and Salmonella Enteritidis. The results of the study showed that the LAB of rumen fluid carried out as an active LAB with Gram positive characteristics, round shape, negative catalase and non motile. Based on the results of testing the antimicrobial activity of lactic acid bacteria from rumen fluid isolates against pathogenic Gram positive (B. cereus and S. aureus) and Gram negative bacteria (Escherichia coli and Salmonella Enteritidis) using well and disc diffusion methods showed that Gram negative bacteria were more sensitive to antimicrobial of LAB compared to Gram positive bacteria. The diameter of the larger inhibition zone is produced using the disc method with the inhibition zone diameter range of 13.66-28.3 mm, while the well method ranges from 0-24.2 mm. The antimicrobial activity of LAB using non filtrate BAL produce inhibition zone diameter size range of 0-26.1 mm, while the filtrate BAL produce inhibition zone diameter range of 0-28.3 mm with the optimum time to produce antimicrobial activity 48 hours compared to 24 hours after incubation.